The role of microRNAs and long non-coding RNAs in epigenetic regulation of T cells: implications for autoimmunity - Prasad, Soumil; Adivikolanu, Harini; Banerjee, Abhinav; Mittal, Mannat; Lemos, Joana R. N.; Mittal, Rahul; Hirani, Khemraj (Frontiers in Immunology, 2025)
Non-coding RNAs (ncRNAs), comprising microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), are increasingly recognized as central regulators of epigenetic programming in T lymphocytes with critical implications for immune tolerance and autoimmunity. We conducted a systematic review to investigate the influence of non-coding RNAs on DNA methylation, histone modifications, and chromatin accessibility in T cells across diverse autoimmune diseases. The majority of studies identified consistent patterns of dysregulation, including increased expression of miR21, miR148a, and miR155, and decreased expression of miR146a, GAS5, and IL21AS1. These alterations were associated with hypomethylation of proinflammatory gene loci, reduction of repressive histone marks, and increased chromatin accessibility at promoters of genes driving pathogenic T cell responses. Mechanistic data from both human and animal models demonstrated that microRNAs frequently regulate the abundance or activity of DNA methyltransferases and upstream signaling molecules, whereas long non-coding RNAs influence the recruitment or activity of chromatin modifying complexes, serve as scaffolds for transcriptional regulators, or function as competitive endogenous RNAs. Experimental manipulation of these non-coding RNAs attenuated disease-associated epigenetic and functional changes in T cells, supporting a causal role in autoimmune pathogenesis. Collectively, the non-coding RNAs as potential biomarkers of disease activity and as therapeutic targets capable of restoring physiological epigenetic regulation in a cell type specific manner. Future research should prioritize longitudinal and single cell multiomics approaches to delineate the dynamic interactions between non-coding RNAs and the chromatin landscape in order to accelerate the translation of these findings into targeted RNA based interventions for autoimmune diseases.Systematic review registrationhttps://inplasy.com/, Identifier INPLASY202580041.